2009
DOI: 10.1055/s-0028-1088135
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanoparticles as an Efficient Catalyst for the One-Pot Synthesis of α-Amino Phosphonates

Abstract: Zinc oxide nanoparticles (ZnO NPs, ca. 22 nm) were used as an effective catalyst in the solvent-free, three-component couplings of aldehydes, aromatic amines and dialkyl phosphites at room temperature to produce various a-amino phosphonates. Compared to known methods, satisfactory results were obtained with high yields through a simple experimental procedure. The catalyst was recycled and reused five times with minor decrease in its catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…In the literature, Agawane and Nagarkar reported synthesis of a-amino phosphates by CeO 2 nanoparticle [23], whereas Hosseini-Sarvari reported it by using TiO 2 [24]. The same reaction was reported by kassaee and co-workers using nanocrystalline ZnO [25], where nanoparticles were synthesized by 'solid state reaction method' reported by Zhu and co-workers [26]. Under same optimized parameters we checked the applicability of ZnONPs synthesized by concentrated solar energy.…”
Section: Evaluation Of Catalytic Activity Of Znonps Preparedsupporting
confidence: 66%
“…In the literature, Agawane and Nagarkar reported synthesis of a-amino phosphates by CeO 2 nanoparticle [23], whereas Hosseini-Sarvari reported it by using TiO 2 [24]. The same reaction was reported by kassaee and co-workers using nanocrystalline ZnO [25], where nanoparticles were synthesized by 'solid state reaction method' reported by Zhu and co-workers [26]. Under same optimized parameters we checked the applicability of ZnONPs synthesized by concentrated solar energy.…”
Section: Evaluation Of Catalytic Activity Of Znonps Preparedsupporting
confidence: 66%
“…Therefore, nanoparticles can dramatically enhance the contact between reactants and catalyst and mimic the homogeneous catalysts [28]. Among several studies in this area, transitionmetal oxide nanoparticles, specifically zinc oxide nanoparticles (ZnO NPs), have great potential as a professional catalysis in various organic transformations due to their high surface to volume ratio, easy recoverability, and their low cost [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Kassaee et al reported that zinc oxide nanoparticles were used as an effective catalyst in the solvent-free, three-component couplings of aldehydes, aromatic amines and dialkyl phosphites at room temperature to produce various α-amino phosphonates. Major advantages with this protocol include short reaction times, mild reaction conditions, easy workup and generality (Scheme 16) (Kassaee et al, 2009 More recently, the author has utilized the nano ZnO catalyst for synthesis of aminophosphonic esters bearing a ferrocenyl moiety revealed that only few papers have been published on the synthesis of these compounds . To expand the scope of this novel transformation, the author used nano ZnO as catalyst for the synthesis of a range of new ferrocenyl aminophosphonates.…”
Section: Synthesis Of Aminophosphonatesmentioning
confidence: 99%